2013
DOI: 10.3109/17435390.2013.780108
|View full text |Cite
|
Sign up to set email alerts
|

Combined repeated-dose toxicity study of silver nanoparticles with the reproduction/developmental toxicity screening test

Abstract: Combined repeated-dose toxicity study of citrate-capped silver nanoparticles (7.9 ± 0.95 nm) with reproduction/developmental toxicity was investigated in rats orally treated with 62.5, 125 and 250 mg/kg, once a day for 42 days for males and up to 52 days for females. The test was performed based on the Organization for Economic Cooperation and Development test guideline 422 and Good Laboratory Practice principles. No death was observed in any of the groups. Alopecia, salivation and yellow discolouration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 26 publications
3
33
0
5
Order By: Relevance
“…Our results show that 6-19-day oral repeated dosing of AgNPs during pregnancy caused oxidative stress in maternal hepatic tissues, as evidenced by a decrease in liver CAT and ↓GSH activities at a dose of 0.5 and 1 mg/kg/day, but did not cause any significant developmental toxicity in same dose in Swiss Albino mice. In contrast, no changes in liver function parameters or histopathology were reported in past combined repeated-dose toxicity study of AgNPs with reproductive/developmental toxicity [25]. Hadrup et al [26] also reported that 28-day repeated oral dose of 9 mg AgNPs/kg/day did not induce any hepatotoxic effects in rats.…”
Section: Discussionmentioning
confidence: 88%
“…Our results show that 6-19-day oral repeated dosing of AgNPs during pregnancy caused oxidative stress in maternal hepatic tissues, as evidenced by a decrease in liver CAT and ↓GSH activities at a dose of 0.5 and 1 mg/kg/day, but did not cause any significant developmental toxicity in same dose in Swiss Albino mice. In contrast, no changes in liver function parameters or histopathology were reported in past combined repeated-dose toxicity study of AgNPs with reproductive/developmental toxicity [25]. Hadrup et al [26] also reported that 28-day repeated oral dose of 9 mg AgNPs/kg/day did not induce any hepatotoxic effects in rats.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, nanosilver is sometimes intentionally included in consumer products for preventing bacterial contamination during their use. According to Hong et al (2013), nanosilver is also considered as a potential additive to animal feed.…”
Section: Biocidal Productsmentioning
confidence: 99%
“…Very recently, the results of a combined repeated-dose toxicity study with the Reproduction / Developmental Toxicity Screening Toxicity Test according to OECD TG 422 for Ag-NP became available (Hong et al 2013). Citrate capped Ag-NP (8 nm) were applied by gavage at doses of 62.5, 125 and 250 mg/kg bw/d to males 14 days prior to mating and 28 days during and after mating, and to females 14 days prior to mating, during mating and gestation, and during 4 days of lacatation.…”
Section: In Vivo Reproductive and Developmental Toxicitymentioning
confidence: 99%
“…66 In addition, oral administrations of silver NPs (250 mg/kg) caused a relatively low toxic effect. 67 Unpublished 90-day repeated oral-dose and genotoxicity data from our previous studies are briefly summarized, as follows. The ZnO NPs did not cause any significant changes at the endpoints of repeated-dose toxicity, including clinical observation, functional observation, body-weight gain, water and food consumption, urinalysis, hematology, serum biochemistry, organ weight, toxicokinetic study, tissue distribution, and histopathology in the repeated study.…”
mentioning
confidence: 99%